Modelling and simulating a batch reactor used in kerosene oxidation desulphurization - Enas.A. eltnay; Nasser. A. Altoumi, Gummaa A. Abodera; Amani kwadikha (Surman Journal of Science and Technology, 2025)
The presence of S-compounds in the petroleum fractions of the oil compounds causes pollution to the environment and operation problems such as corrosion and sulfur dioxide sulfur dioxide (SO2) production that increases acid rain. Though catalytic hydrodesulfurization (HDS) is also often used to remove these compounds, it is necessary to use hydrogen and high pressures which results in high energy and operation costs. This paper has proposed an in-depth mathematical model based on kinetic data acquired experimentally to process the simulation of the oxidative desulfurization (ODS) of the kerosene in batch reactor. The model itself was only conducted within MATLAB R2024a which allowed the optimization of numerical process parameterization. The best kinetic constants were named as activation energy of 19.14 kJ/mol, pre-exponential factor of 2163.56 (wt)-0.66530 min-1 and reaction order of 1.67. Such parameters have helped in the reaction conditions that took a sulfur conversion of more than 99.9 % and these are 370 K and 120 minutes. Also, a scale-up study has shown that an efficient working diameter of the reactor is 1 meter with the optimized conditions applied.